Analisis Pertumbuhan Ekonomi dan Pengeluaran Pemerintah Terhadap Pegerakan Investasi Provinsi Riau - Ranti Darwin; Wan Laura Hardilawati (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Riau, 2018)
The purpose of this study was to determine the effect of economic growth and government expenditure on investment in Riau Province. The data type of this research is time series data. In addition, it uses secondary data published by the Central Bureau of Statistics (BPS) of Riau Province. This study uses the data analysis in the form of multiple linear regression analysis using EVIEWS 9.0 software. The results of this study indicate that economic growth has a significant influence with a negative relationship to investment in Riau Province. While government expenditure has a non-significant and negative relationship to investment in Riau Province. In addition, this study also explains that together economic growth and government expenditure have a significant relationship to investment. The results of this study also suggest the need for good management in managing the drivers of investment in Riau Province to create better economic development.